2009
DOI: 10.1038/nn.2373
|View full text |Cite
|
Sign up to set email alerts
|

Change detection by thalamic reticular neurons

Abstract: The thalamic reticular nucleus (TRN) is thought to function in the attentional searchlight. We analyzed the detection of deviant acoustic stimuli by TRN neurons and the consequences of deviance detection on the TRN target, the medial geniculate body (MGB) of the rat. TRN neurons responded more strongly to pure-tone stimuli presented as deviant stimuli (low appearance probability) than those presented as standard stimuli (high probability) (deviance-detection index = 0.321). MGB neurons also showed deviance det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
147
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(157 citation statements)
references
References 33 publications
9
147
0
1
Order By: Relevance
“…It is an exciting feature of the auditory thalamus that the potential strength of SSA is anatomically segregated. So far, SSA in the vMGB as part of the lemniscal auditory pathway could not be detected at all (Ulanovsky et al, 2003(Ulanovsky et al, , 2004 or showed SSA only to a relatively limited degree (Anderson et al, 2009;Yu et al, 2009;Antunes et al, 2010). Here, we present significant SSA in the gerbil vMGB with an average DS differences of ϳ15%, which is comparable with the 30% described for the rat MGB as a whole (Yu et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is an exciting feature of the auditory thalamus that the potential strength of SSA is anatomically segregated. So far, SSA in the vMGB as part of the lemniscal auditory pathway could not be detected at all (Ulanovsky et al, 2003(Ulanovsky et al, , 2004 or showed SSA only to a relatively limited degree (Anderson et al, 2009;Yu et al, 2009;Antunes et al, 2010). Here, we present significant SSA in the gerbil vMGB with an average DS differences of ϳ15%, which is comparable with the 30% described for the rat MGB as a whole (Yu et al, 2009).…”
Section: Discussionsupporting
confidence: 72%
“…It is well known that the auditory cortex adjusts and improves signal processing at subcortical stages through frequency-dependent facilitation and inhibition acting on different timescales from short-term changes to long-term plasticity (He, 2003a;Yan et al, 2005;Winer, 2006;Suga, 2008). This makes it rather likely that the strong effects of SSA in the auditory cortex are relayed to the vMGB directly or via corticofugal projections to the inferior colliculus (IC) and the thalamic reticularis nucleus (TRN) in which, again, SSA has already been described (Malmierca et al, 2009;Yu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the relevant depressing synapse may actually be at the collicular inputs to the thalamus. Additional thalamic mechanisms may be in play, like the strong interactions between the MGB and the thalamic reticular nucleus (40).…”
Section: Discussionmentioning
confidence: 99%
“…How neural systems detect such deviant sounds remains poorly understood, but it is known that this context-dependent task is achieved preattentively, at least in part. Auditory neurons in cats (Ulanovsky et al, 2003(Ulanovsky et al, , 2004 and rodents (Pérez-González et al, 2005;Anderson et al, 2009;Malmierca et al, 2009;von der Behrens et al, 2009;Yu et al, 2009;Antunes et al, 2010) habituate on short timescales to probabilistically recurring tones in a frequency-selective way [stimulus-specific adaptation (SSA)], so that responses are stronger when tones are deviant. This phenomenon is hypothesized to be involved in the "automatic" detection of deviant sounds in natural auditory scenes (Nelken and Ulanovsky, 2007).…”
Section: Introductionmentioning
confidence: 99%